Major Depression in Comorbidity with Substance use Disorders: Patients’ Features and Clinical-Neurobiological Rationale of Antidepressant Treatments - De Filippis, Sergio; Martinotti, Giovanni; Nicoletti, Ferdinando; Mastrostefano, Andrea; Trovini, Giada; Pugliese, Anna; Di Nicola, Marco (Current Neuropharmacology, 2025)
The frequent co-occurrence of major depressive disorder (MDD) and substance use disorders (SUDs) entails significant clinical challenges. Compared to patients with MDD alone, patients with MDD and SUD often show increased anhedonia, emotional blunting, and impaired cognitive function. These symptoms lead to an inability to control cravings, more substance use, increased relapse rates, and poor adherence to the treatment. This fosters a detrimental cycle leading to more severe depressive symptoms, functional impairment, and chronicity, culminating in heightened morbidity, mortality, and healthcare resource utilization. Data on antidepressant treatment of MDD-SUD patients are inconclusive and often conflicting because of a number of confounding factors in clinical trials or difficulty in dissecting the specific contributions of pharmacological versus psychological interventions in real-world studies. The patient's unique clinical features and specific SUD and MDD subtypes must be considered when choosing treatments. Ideally, drug treatment for MDD-SUD should act on both conditions and address core symptoms such as anhedonia, craving, and cognitive dysfunction while ensuring minimal emotional blunting, absence of drug interactions, and no addictive potential. This approach aims to address unmet needs and optimize the outcomes in a clinical population often underrepresented in treatment paradigms.
Keywords: antidepressants